MEMS microrelay design, modeling, and simulation - Yap, David
The objective of this project is to design a microrelay base on piezoelectric actuation method in MEMS technologies. After that, a virtue prototyping is modeled for simulation and analysis with the existing CAD tools and then set to seek for any possible optimization method to improve the performance of the design or suit to the potential application requirement as the solution to overcome the deficiency of the existing relays.